INTEGRATED REPORTS AND LEGITIMACY THEORY - Herz, Jeannette M. (2020)
The author explains the evolution of what a report has inside until it became into an Integrated Report, in response to the need of legitimacy of the companies. The International Integrated Report Council (IIRC), created in 2010, proposed a referential frame for identifying the information to be included in an Integrated Report in order to assess the capacity of an organization to create value and to obtain “organizational legitimacy”.